Inovasi Media Pembelajaran Mata Pelajaran Al Qur’an Hadits - Iskandar Zulkarnain (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
The reseach to know about 1) how to The use of image media in learning Al Qur’an Hadith at Madrasah Aliyah Mazroillah in Lubuklinggau City? 2) how the results of learning Al Qur’an Hadith at Madrasah Aliyah Mazroillah in Lubuklinggau City. The results of this study indicate that: 1) The use of image media in learning Al Qur’an Hadith at Madrasah Aliyah Mazroillah in Lubuklinggau City can be said to have been used, although only visual media and audio visual media are used. 2) The results of learning Al Qur’an Hadith at Madrasah Aliyah Mazroillah in Lubuklinggau City can be said to be satisfying because students are more interested in learning activities compared to learning without using learning media. 3) Inhibiting factors in the form of facilities and infrastructure and support for the implementation of learning Al Qur’an Hadith subject using learning media at Madrash Aliyah Mazroillah Lubuklinggau, namely the ability of teachers and the development of learning innovations.